Exploring and Implementing a Cross-Disciplinary Innovation Talent Cultivation Model for Professional Master’s Programs in Civil and Hydraulic Engineering - Yaping Ge; Guoping Huang; Jing Liu (Journal of Advanced Research in Education, 2025)
With the rapid development of social economy, the demand for professionals in civil and hydraulic engineering is increasing daily. The traditional model for cultivating professional master’s talents is no longer meet the diverse requirements of the market. This paper explores the implementation of a cross-disciplinary innovation Guidance model in the master’s education of civil and hydraulic engineering. By analyzing the current challenges in talent cultivation, the paper outlines objectives for talent development, curriculum design, practical teaching methodologies, and strategies for fostering innovative capabilities within the context of Cross-disciplinary innovation Guidance. Additionally, it provides recommendations for effectively implementing this model, aiming to serve as a reference for nurturing high-quality, innovative talents equipped with practical skills.